2020
DOI: 10.1186/s12877-020-01669-7
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-measured and self-reported physical activity in relation to extraversion and neuroticism: a cross-sectional analysis of two studies

Abstract: Background: Personality reflects relatively stable and pervasive tendencies in feeling, thinking and behaving. While previous studies have found higher extraversion and lower neuroticism to be linked to higher self-reported physical activity levels, larger studies using accelerometer-measured physical activity are lacking. This study investigated the cross-sectional associations of extraversion and neuroticism with both accelerometer-measured and self-reported physical activity and the role of these personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
8
15
0
Order By: Relevance
“…The present study demonstrated that among Japanese working women, higher extraversion was associated with desirable physical activity habit and daily fruit consumption and higher conscientiousness was associated with low-risk alcohol consumption habits and daily fruit consumption. However, non-working women exhibited higher extraversion and lower neuroticism in association with desirable physical activity habits, in line with previous research ( Kekäläinen et al, 2020 ). This difference might depend on personality trait, employment status, or other individual factors.…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrated that among Japanese working women, higher extraversion was associated with desirable physical activity habit and daily fruit consumption and higher conscientiousness was associated with low-risk alcohol consumption habits and daily fruit consumption. However, non-working women exhibited higher extraversion and lower neuroticism in association with desirable physical activity habits, in line with previous research ( Kekäläinen et al, 2020 ). This difference might depend on personality trait, employment status, or other individual factors.…”
Section: Discussionsupporting
confidence: 91%
“…As indicated by previous studies that personality factors, such as the Big Five, contribute to inter-individual variability in physical activity [22][23][24], our study revealed that the extraversion score and conscientiousness score was positively and was negatively associated with human mobility, respectively. In addition, our study found that ego resiliency as a factor of personality, which has received attention in the field of mental health, Not surprisingly, people who used public transportation and rode bicycles had greater LSA scores, although a previous study indicated that there was no association between the use of public transportation and outings [7].…”
Section: Effects Of Individual Factors On Human Mobilitysupporting
confidence: 78%
“…Note. PERSONALITY AND MEMORY DISCREPANCY (Kekäläinen, Laakkonen, et al, 2020). In the however, extraversion was not associated with discrepancy between self-reported and accelerometer-measured leisure time physical activity.…”
Section: Discussionmentioning
confidence: 82%
“…For example, individuals who scored high on neuroticism tended to overestimate their actual weight, while extraverts tended to underestimate their actual weight (Sutin & Terracciano, 2016). Furthermore, individuals who score high on neuroticism were more likely to underestimate their leisure time physical activity compared to accelerometer-measured leisure time physical activity (Kekäläinen, Laakkonen, et al, 2020). In the same study, however, extraversion was not associated with discrepancy between self-reported and accelerometer-measured leisure time physical activity.…”
Section: Discussionmentioning
confidence: 99%